PERSIAPAN, PELAKSANAAN, DAN PENYELESAIAN KEGIATAN OUTBOUND DI SEKOLAH DASAR - Khusna, Mufidatul; Rahmawati, Debby; Nasrullah, Mohammad Altof; Rahayu, Hesthi Putri Budi; Sumadi, Conny Dian (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
This study aims to describe the preparation, implementation, and completion of outbound activities in elementary schools. The method used in this study is a literature study with ten articles relevant to the topic of preparation, implementation, and completion of outbound activities in elementary schools. Data analysis techniques are carried out by data reduction, data presentation, and triangulation. Based on the results of the study, it was concluded that the preparation that must be done by a teacher before carrying out outbound activities includes: (1) determining the purpose of holding outbound, (2) determining the form of activities or materials to be carried out, of course, the material or activities must be adjusted to the objectives, (3) making plans, including the time of implementation, location, transportation, consumption, and budget as well as the formation of an implementing committee, (4) surveying the location to be used, (5) prepare equipment and equipment to be used, (6) explanation of outbound activities to be carried out to students and parents so that they can make preparations, and (7) risk evaluation. Furthermore, when arriving at the outbound location the teacher must do things that include: (1) explaining the procedures for outbound games and activities, (2) dividing students into groups, (3) guiding students in carrying out activities, (4) controlling and observing students in carrying out activities to be more orderly and in accordance with the planning and rules of the game, (5) coordinating with the committee or other teachers if things happen that are not desirable. As for after the outbound activities are completed, teachers must do several things including: (1) packing and returning all equipment that has been used, (2) cleaning locations that have been used for outbound activities, (3) reflection, evaluating all activities that have been carried out during outbound, (4) preparing accountability reports (LPJ).